THE ANALYSIS COMPARISON OF BASALT VIA MELTING PROCESS FROM MATARAM BARU (EAST LAMPUNG) WITH SLOW AND FAST COOLING METHOD OVER XRD APPROACH - David Candra; Kusno Isnugroho; Yusup Hendronursito; Muhammad Amin; Muhammad Al Muttaqii (MULTITEK INDONESIA, 2020)
The process of melting basalt stone from Mataram Baru, East Lampung has been carried out over a mini shaft furnace with a temperature of 1600 ˚C. Basalt stone with the smelting process was modified with slow and fast cooling methods. Based XRD result shows the methods were significant applied to the liquid of basalt stone. By a slow cooling process, the crystal structure is unchanged from the original material but the mechanical characteristics increased. While by a fast cooling process, the amorphous crystal structure and weak mechanical properties are obtained from the original material. The results show, both products have a great potential to be used as advanced material. With a slow cooling process, it can be applied as a friction resistant material while by fast cooling method, the products can be used as ceramic materials.